Synthesis and Characterization of Poly(NIPAM-co-AA) Polymers Possessing Perfluorinated Side Chains and Chemically Linked Pyrene Labels - Pokhrel, Megh Raj; Bossmann, Stefan H. (Journal of Nepal Chemical Society, 2012)
The synthesis of Poly(n-isopropylacrylamide–co-acrylic acid)/-Poly(NIPAM-co-AA) polymers featuring perfluorinated side chains as well as chemically linked pyrene fluorescence labels has been reported. The resulting polymers have been characterized with the aid of UV/VIS, FTIR spectroscopy and Gel permeation chromatography. DOI: http://dx.doi.org/10.3126/jncs.v27i1.6663 J. Nepal Chem. Soc., Vol. 27, 2011 67-73